Розробка telegram-боту для введення заявок в перукарні - Шматко, А. І. (ХНУРЕ, 2024)
This study focuses on the development of a Telegram chatbot for hair salons to interact with clients, addressing the declining profitability of traditional beauty establishments. Using the Telegram Bot API and C#, the research explores communication processes between salon administrators and clients, employing theoretical and computational methods. The study aims to provide a cost-effective communication tool for enhancing business engagement and customer loyalty within the beauty industry.
Keywords: telegram-бот; перукарня; система автоматизація запису